THE UNIVERSITY ELECTRONIC SPACE AS THE BASIS FOR IMPLEMENTING NEW EDUCATIONAL TECHNOLOGIES - Galina A. Berulava; Anna V. Druzhinina; Ekaterina V. Belyaeva; Viktor G. Malysh; Tamara S. Pil’Shchikova; Sagira K. Istalieva; Lidiya R. Kadyrova (Высшее образование в России)
The article deals with the developed and implemented at the International Innovative University new electronic learning technologies giving the effect of «social learning.» These technologies are characterized by open information and communication space supported by multimedia learning tools and hypermedia.